Incomplete epidemiological transition in Kazakhstan: changes in the structure of life expectancy and causes of death (Хабаршы. Психология және социология сериясы, 2025)
This article examines Kazakhstan's epidemiological transition, focusing on shifts in mortality patterns and life expectancy within the context of socioeconomic and demographic influences. The study aims to explore the evolution of Kazakhstan's population mortality from 1991 to 2022, encompassing both age-standardized and cause-specific mortality rates, and the corresponding changes in life expectancy. The author set the task of determining which stage of the epidemiological transition Kazakhstan is currently at and identify the key factors influencing the present situation. This topic is important for understanding the dynamics of mortality and health of the population in the context of economic and social changes in the country.Understanding the complex relationship between death rates, public health, and the changing economic and social fabric of a country is essential to this field of study. This not only helps to systematize the changes in mortality and life expectancy but also provides understanding of the mechanisms these changes, as well as the impact of socio-economic and demographic factors.The research methodology includes a comparative analysis of official mortality statistics, the use of age and standardized rates, and the calculation of life tables. For a more detailed analysis, the decomposition method was applied, enabling the identification of cause-and-effect relationships in the changes in life expectancy and mortality for the main causes of death.Analyzing mortality rates using decomposition methods in the period from 2010 to 2022, the main factors influencing fluctuations in life expectancy in Kazakhstan were diseases of the circulatory system, injuries and external causes, as well as cancers and neoplasms.The article's practical significance lies in its utilization of study data to formulate recommendations for enhancing health systems and social policies, decreasing mortality, and raising life expectancy.Keywords: epidemiological transition, causes by death, age-specific and standardized mortality rates, life expectancy at birth.